Research on Well Area Connectivity of Carbonate Gas Reservoir in Eastern Sichuan Basin—A Case Study of Wubaiti Block - Jiang, Yandong; Chen, Liang; Zhou, Tuo; You, Liangrong; Chu, Guangzhen; Ren, Dazhong; Zhou, Zhaohua (Frontiers in Physics, 2022)
Carbonate gas reservoirs in the eastern Sichuan Basin are featured by low matrix permeability, well-developed fractures, caves and faults, which result in complicated fluid flow and connectivity. The Wubaiti Carboniferous gas reservoir is an earlier developed block in Eastern Sichuan with a development history of 27 years. The geological features, e.g., block structure and fault development, have been extensively studied, but a few studies address the connection relationship and gas-water interface of the DT 2 well area in the north. To solve this problem, this paper proposes a reserve simulation method based on the conventional connectivity analysis, which calculates the reserves of different gas-water interfaces in the well area. Combined with production performance analysis, the well-controlled reserves and drainage area were also determined. The analysis verifies the connectivity between wells. Integrating with interference testing, fluid properties, seismic and geological data, the connection relationship between well areas is further clarified. The results show that the northern water bodies of the DT 2 well area consist of two independent and disconnected water bodies. There is a blocking zone between the DT 2 and DT 3 and DT 4 wells, which causes the disconnection of water bodies but the connection of gas. The results also indicates that the eastern water body of the main area and the eastern water body of the DT 2 well area are part of a uniform water body with a uniform gas-water interface. The research method has a significance for the connectivity research of similar gas reservoirs.